Magnetic resonance spectroscopy of the ischemic brain under lithium treatment. Link to mitochondrial disorders under stroke. (25th July 2015) - Silachev, Denis N.; Gulyaev, Mikhail V.; Zorova, Ljubava D.; Khailova, Ljudmila S.; Gubsky, Leonid V.; Pirogov, Yury A.; Plotnikov, Egor Y.; Sukhikh, Gennady T.; Zorov, Dmitry B.
Highlights: Mitochondrial functioning is changed by ischemia and associated acidification. Brain ischemia–reperfusion leads to increase in lactate and myo-inositol. Ischemia–reperfusion causes a moderate decrease in N-acetylaspartate. Administration of LiCl in the reperfusion phase normalized the levels of metabolites. LiCl markedly reduces infarct size, brain swelling and behavioral dysfunction. Abstract: Recent evidence suggests that mitochondria are one of the main factors in the pathogenesis in different organs including brain. The pathogenesis after brain damage is caused not only by the change in bioenergetics, but also involves impairment of alternative functions of mitochondria, particularly those related to the control of cell death. In this study we evaluated partial metabolic pathways under the simulation of a stroke by using the occlusion of the middle cerebral artery in rats. The analysis shows that the induced switch to a non-oxidative energy metabolism (glycolysis) due to the block of tissue oxygen supply does not ensure the adequate supply of the tissue with ATP. Moreover, the well-known acidification of the ischemic tissue is not associated with the so-called traditionally and incorrectly considered "lactic acidosis" (the generation of lactate from glucose by itself does not lead to excessive generation of protons), but occurs because of the consumption of tissue ATP under its reduced resynthesis. Incubation of mitochondria isolated from normal rat brain at neutral and slightly acidic pH, mimicking the intracellular pH of normal and ischemic tissues correspondingly, revealed serious changes in mitochondrial bioenergetics, partially reflected in the magnitude of respiratory control and the basal and maximally stimulated respiration rates. Measurement of available metabolites by 1 H MR spectra of normal and ischemia-damaged brains showed a significant increase in lactate and myo-inositol and a moderate decrease in N-acetylaspartate 24 h after reperfusion. Remarkably, the administration of lithium chloride in the reperfusion phase normalized the levels of metabolites. Moreover, the introduction of lithium salts (chloride or succinate) in the bloodstream, restored after ischemia, reduced both the size of the ischemia-induced brain damage and the degree of brain swelling. Besides, post-ischemic introduction of lithium salts largely restored the neurological status of the animal.